Development of an E-Worksheet on Acid-Base Material with the Sorogan-Bandongan Learning Model to Train Students Attitude of Responsibility - Naimah, Kholifatul; Rinaningsih, Rinaningsih (Jurnal Pijar Mipa, 2025)
The Sorogan-Bandongan learning model is a traditional approach that is effective in training learners' responsibility through a series of learning activities, including reading and working on handouts, diagnostic tests, independent practice based on test results, reinforcement of concepts by the teacher, and self-reflection. This model emphasizes both individual (Sorogan) and collective (Bandongan) approaches, so that students are not only responsible for tasks they complete independently but also participate in collaborative discussion and evaluation processes. The purpose of this study is to describe the feasibility of the E-Worksheet on acid-base material using the Sorogan-Bandongan learning model to cultivate students' sense of responsibility. The feasibility of the E-Worksheet is assessed based on validity, practicality, and effectiveness. The method used in this study is Research and Development (R&D) with Thiagarajan's 4D development model, limited to the Develop stage. In this study, a limited pilot test was conducted in May 2025 with 20 high school students from SMA Negeri 19 Surabaya who had already studied acid-base material. Based on the results of the research conducted, it was found that the validity of the E-Worksheet was deemed valid based on the scores obtained from the validation sheet. The overall results of student activities from meeting 1 to meeting 3 showed an increase and obtained a percentage of ≥ 61%, indicating that the E-Worksheet on acid-base material is practical. The effectiveness of the E-Worksheet was assessed based on the increase in the observation sheet scores for students' sense of responsibility in each session. The n-gain results for students' sense of responsibility were categorized as high. Based on these results, it can be concluded that the E-Worksheet on acid-base material using the Sorogan-Bandongan learning model to cultivate students' sense of responsibility is suitable for use.